FAKTOR-FAKTOR YANG MEMPENGARUHI PREDIKSI PERINGKAT OBLIGASI DITINJAU DARI FAKTOR AKUNTANSI DAN NON AKUNTANSI - MAGRETA MAGRETA; POPPY NURMAYANTI (Jurnal Bisnis dan Akuntansi, 2009)
This research aims at providing empirical evidance on factor that affect obligation ratings prediction. This study examines the role of accounting data and non accounting data in predicting the accurance of obligation ratings. The accounting data consist of firm size, liquidity, profitability, leverage and productivity. The non accounting data consist of secure, maturity, and auditor reputation. The samples of this research consist of 80 firms are listed in PT. PEFINDO from 2005 to 2008 except Bank and Financial Institution, Securities Company and Other Finance. Logit regression is used to test the hypothesis. The finding of this research, 1) Firm Size, Liquidity, Leverage, Maturity and Auditor Reputation are insignificant variables determining obligation ratings and 2). Profitability, Productivity and Secure are significant variables determining obligation ratings. The result indicates that in general, the obligation of Indonesia firms are investment grade.